2001
DOI: 10.1016/s0304-4017(01)00410-1
|View full text |Cite
|
Sign up to set email alerts
|

A multiplex PCR assay for differentiating economically important gastrointestinal nematodes of cattle

Abstract: A multiplex polymerase chain reaction (PCR) test was developed for identifying gastrointestinal (GI) nematodes that commonly infect cattle. This assay was developed using adult-derived genomic DNA and shown capable of discriminating parasite eggs from the feces of experimentally-infected animals at both the species and genus levels. Sequence data from internal (ITS) and external (ETS) transcribed spacers of the ribosomal DNA (rDNA) repeats as well as the 3'-end of the small subunit rDNA and 5'-end of the large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
58
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 18 publications
0
58
0
1
Order By: Relevance
“…Trichostrongyle eggs can be differentiated by faecal culture and identification of the larva (van Wyk et al, 2004). PCR techniques can also be employed for a variety of systems such as gastrointestinal nematodes of cattle (Zarlenga et al, 2001) or taeniid eggs observed in dog faeces (Trachsel et al, 2007). For certain parasites such as Schistosoma haematobium urine examination can be used to detect eggs.…”
Section: Prevalencementioning
confidence: 99%
“…Trichostrongyle eggs can be differentiated by faecal culture and identification of the larva (van Wyk et al, 2004). PCR techniques can also be employed for a variety of systems such as gastrointestinal nematodes of cattle (Zarlenga et al, 2001) or taeniid eggs observed in dog faeces (Trachsel et al, 2007). For certain parasites such as Schistosoma haematobium urine examination can be used to detect eggs.…”
Section: Prevalencementioning
confidence: 99%
“…The development of the multiplex PCR gave the opportunity to diagnose in a single reaction different nematode genera and/or species (ZARLENGA et al, 2001). Such approach, associated with the development of the Real-time PCR assays, created the opportunity to refine the diagnosis incorporating quantification of the DNA in a given sample, i.e., indicating the proportion of each genus or species in each sample (SAMSON-HIMMELSTJERNA et al, 2002;BOTT et al, 2009).…”
Section: Influence Of the Rate Of Infection And The Immune Response Omentioning
confidence: 99%
“…The PCR technique has been used to detect DNA of diverse organisms, facilitating the biological diagnosis of the parasites in tissues and secretions. Through PCR technique were able to genetically differentiate Haemonchus contortus from Haemonchus placei [4]. The use of this technique for the investigation of DNA of Echinococcus multilocularis in fecal samples of fox [5] allowed sensible and specific diagnosis for infections caused by this parasite.…”
Section: Introductionmentioning
confidence: 99%